2000
DOI: 10.1021/es9914339
|View full text |Cite
|
Sign up to set email alerts
|

Relative Potencies of Individual Polychlorinated Naphthalenes and Halowax Mixtures To Induce Ah Receptor-Mediated Responses

Abstract: Polychlorinated naphthalenes (PCNs) are ubiquitous environmental pollutants that are structurally similar to other polychlorinated diaromatic hydrocarbons (PCDHs), such as polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs), and biphenyls (PCBs). Despite being ubiquitous, much less is known about the fate, transport, and biological effects of individual PCN congeners than other PCDHs. The purpose of the current study was to utilize an in vitro assay (H4IIE-luc) to determine potencies relative to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
166
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(170 citation statements)
references
References 53 publications
3
166
1
Order By: Relevance
“…The concentrations of PCNs emitted from waste incinerators in this study were higher than those of five MSW incinerators reported by Abad et al (1999), but lower than that of raw gas from a MSW incinerator reported by Oh et al (2007). The dioxin-like toxicity of PCNs has been investigated in previous studies (Hanberg et al 1990;Blankenship et al 2000;Villeneuve et al 2000). The relative potency factors (RPFs) of individual PCN congeners to 2378-TCDD estimated in these studies have been used to evaluate the toxicity of PCNs (Noma et al 2004;Guo et al 2008;Liu et al 2009).…”
Section: Concentration Of Pcns Emitted From Waste Incinerators Investcontrasting
confidence: 44%
“…The concentrations of PCNs emitted from waste incinerators in this study were higher than those of five MSW incinerators reported by Abad et al (1999), but lower than that of raw gas from a MSW incinerator reported by Oh et al (2007). The dioxin-like toxicity of PCNs has been investigated in previous studies (Hanberg et al 1990;Blankenship et al 2000;Villeneuve et al 2000). The relative potency factors (RPFs) of individual PCN congeners to 2378-TCDD estimated in these studies have been used to evaluate the toxicity of PCNs (Noma et al 2004;Guo et al 2008;Liu et al 2009).…”
Section: Concentration Of Pcns Emitted From Waste Incinerators Investcontrasting
confidence: 44%
“…The dioxin-like toxicity of PCNs has been investigated in previous studies. 21 −23 The relative potency factors (RPFs) of individual PCN congeners to 2378-TCDD estimated in these studies have been used to evaluate the toxicity of PCNs. 14,24,25 In this study, the TEQs of PCNs were defined by the sum of the products of the concentration of each congener multiplied by its RPF reported by Noma et al 24 (Table S2 of the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Polychlorinated naphthalenes (PCNs) are often termed as dioxin-like compounds given their similar properties (Weber et al 2008;Blankenship et al 2000). PCNs have attracted increasing attention due to their ubiquitous occurrence in environmental matrices and biota (Harner et al 2006;Bidleman et al 2010).…”
Section: Introductionmentioning
confidence: 99%